Pengaruh budaya organisasi, motivasi, dan kompensasi, terhadap kinerja karyawan melalui kepuasan kerja sebagai variabel intervening - Syahputra, Yoggie Ragis; Sugiono, Edi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
In this modern era, the number of employees (manpower) is abundant, requiring an organization/company to think about how to utilize and optimize employee performance. This study aims to analyze the influence of organizational culture, motivation, and compensation on employee performance through job satisfaction as an intervening variable . This research is a type of quantitative research with the analytical method used is descriptive and inferential analysis with Structural Equational Model (SEM).The data used are primary and secondary data with data collection techniques using a questionnaire technique or questionnaire technique.The results of the study are organizational culture, motivation and compensation have a positive and significant effect on job satisfaction and employee performance, job satisfaction has an effect negative and insignificant effect on employee performance Organizational culture on employee performance has a positive and significant effect on job satisfaction Motivation on employee performance has a positive and significant effect on job satisfaction Compensation for performance Employee work has a positive and significant effect on employee performance through job satisfaction.